2022
DOI: 10.1101/2022.02.18.481036
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Progressive maturation of the root apical meristem inArabidopsis thalianalateral roots

Abstract: Meristems are stem cells niches that support the formation of all plant organs and are either set during embryogenesis and maintained throughout the plant life or specified de novo, post-embryonically. The embryo-derived root apical meristem is organized around a group of infrequently dividing cells, the quiescent centre, that maintains the stem cells, organizes growth along two axes and owing to its resistance to 3ic stress can replace damaged stem cells. In most cases, lateral roots post-embryonically branch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
(148 reference statements)
0
3
0
Order By: Relevance
“…A detailed report of cell divisions during lateral root formation showed that cell expansion is the main driver of lateral root emergence, while cell numbers only increase after emergence, proposing that the new lateral root meristem is only actively dividing after emergence (Malamy and Benfey, 1997). Furthermore, a recent report showed that mitotic quiescence of the quiescent center was only established after emergence, together with establishment of the cellular layout and unique gene expression profiles of the stem cell niche (Berthet et al, 2022). We found that the expression domain of CYP79B3 shifts from a region underlying the lateral root primordia to the meristem of the lateral root after lateral root emergence.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed report of cell divisions during lateral root formation showed that cell expansion is the main driver of lateral root emergence, while cell numbers only increase after emergence, proposing that the new lateral root meristem is only actively dividing after emergence (Malamy and Benfey, 1997). Furthermore, a recent report showed that mitotic quiescence of the quiescent center was only established after emergence, together with establishment of the cellular layout and unique gene expression profiles of the stem cell niche (Berthet et al, 2022). We found that the expression domain of CYP79B3 shifts from a region underlying the lateral root primordia to the meristem of the lateral root after lateral root emergence.…”
Section: Discussionmentioning
confidence: 99%
“…Before the emergence and formation of a LR, the LRP in Arabidopsis must cross three cell layers: the endodermis, the cortex and the epidermis (Stoeckle et al., 2018). When a LRP forms four cell layers (stage IV), stem cells are defined within the developing apical meristem and the LRP breaks through the endodermis at approximately the same time (Banda et al., 2019; Berthet et al., 2022). This period of pre‐emergent LRP development is accompanied by TTL3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In some plants, QC is specified during LRP outgrowth but in other species, it happens after LR emergence (Torres‐Martínez et al ., 2019). Although the QC is specified at a very early stage of LRP in Arabidopsis , the SCN maturation is a progressive process during LR development (Berthet et al ., 2022). In Arabidopsis , WOX5 is a specific marker of QC and non‐cell‐autonomously regulates the SCN (Box 2; Tian et al ., 2014).…”
Section: Lrp Morphogenesis and Emergencementioning
confidence: 99%